Pasantía en proyectos internacionales con la empresa KUBO Architecture & Engineering, Málaga, España (2019)
The international internships offered by the University of America Foundation in agreement with foreign companies, seek to provide students with an opportunity to expand their work horizons, linking them with international companies in other countries, with the aim of enriching their cultural heritage and establishing connections type of work for the future. Since 2017 they are the second degree option of the Faculty of Architecture, an option in which students can test the knowledge acquired in the university during the five years of training and at the same time acquire knowledge in the areas of design, planning and execution of projects.